Las 'sectas' protestantes y el espíritu del (anti-) imperialismo Entrelazamientos religiosos en las Américas - Schäfer, Heinrich Wilhelm (Ensayos InterAmericanos, 2020)
Latin America, the United States of America, religion, and politics are ingredients of a brew with considerable explosive power. The four terms denote factors in a complex and, for the most part, violently intertwined relationship. Historically, this relation has been shaped primarily by the Protestant mission in Latin America and its Pan-American objectives. Yet, this mission now belongs to the past. The once American religiosity of the missionaries has taken different and more charismatic forms under the conflicting conditions of life in Latin America and today is shaped in particular by the class antagonisms of the subcontinent. However, this does not mean that some evangelical organizations do not continue to represent political interests of their Northern neighbor, or that vice versa,the political religiosity of the South does not contribute to ideological struggles in the United States, either through Liberation Theology in the 1980s, or today through the solidarity with Latin American migrants. The present book visualises the logic of the inter-American entanglements by tracing and interpreting exemplary developments and conflicts, framing the narrative plot between two important religious events in 1916 and 2016.